Infective endocarditis in a patient with hypertrophic obstructive cardiomyopathy: а case report - L. L. Sarkisyan; S. V. Kruchinova; K. V. Skaletsky; A. M. Namitokov; K. O. Barbukhatti; E. D. Kosmacheva (Российский кардиологический журнал, 2025)
Infective endocarditis in patients with hypertrophic cardiomyopathy is a rare clinical combination. However, this combination of diseases increases the already high risk of death in patients with hypertrophic cardiomyopathy. In this regard, early diagnosis of this pathology, timely antibacterial therapy, and, if necessary, surgical treatment are necessary. The article describes a clinical case.